Non-financial factors of performance: the case of mechanical engineering companies in the Czech Republic - Režňáková, Mária; Karas, Michal; Strnadová, Michala (Univerzita Pardubice, 2017)
Successful achievement of strategic goals requires an effective performance management system, i.e. determining the appropriate indicators measuring the rate of goal achievement. These indicators are known as key performance indicators or value drivers according to the principles of value-based management. Performance is monitored by both financial and non-financial indicators. In order to gain further insight into the topic, this paper presents the results of research identifying the non-financial factors that affect the performance of mechanical engineering enterprises in the Czech Republic. The data were obtained from a questionnaire survey of the enterprises’ senior management. The results of the survey were evaluated on the basis of response rate. The evaluation also included a comparison of the managers’ opinions and the performance of their enterprises – measured by return on equity. The results of the analyses show that the factors most detrimental to enterprise performance include the incompetence of responsible employees and the disregard of the customers’ requirements. Factors most frequently shown to increase the value of the enterprise are the product quality, product innovation and flexibility in meeting customers’ requirements.
Keywords: performance measurement; value-based management; value drivers; financial ratios; mechanical engineering; G30; G32